DESKRIPSI KETERAMPILAN PSIKOMOTORIK MAHASISWA PENDIDIKAN KIMIA FKIP UNTAN PADA PRAKTIKUM PENENTUAN KADAR ASAM ASKORBAT - Nurbaiti, Nurbaiti; Enawaty, Eny; Sartika, Rody Putra (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract                                                                                                                                This research aims to describe the psychomotor ability of chemical education students on the determination of ascorbic acid levels by iodimetry method. The research method used is descriptive method with instrument in the form of observation sheet. Data collection techniques used are direct observation and directcommunication. The subjects of the research were chemical education students of FKIP Untan of 2015 consisting of 24 students. The result of the research indicated that the persentage of psychomotor ability of students in the category of good, good, enough, and less in sequence were 8.3%, 33.3%, 41.2%, and 16.7% respectively. In the indicator of the preparation stage of glassware shows the percentage in the excellent category is 100%. In the scour grinding stage indicator shows the percentages in the categories of good, less, and less once sequence were 50%, 25%, and 25% respectively. In the indicator phase weigh the sample shows the percentage in the excellent category that is 100%. In the indicator stage of the titration tool shows the percentage in the category of both well and well in sequence that is 83.3% and 16.7%. in indicator of flushing burette stage showed percentage in good category and less once sequentially that is 8.3% and 91.7%. In the indicator stage of pouring raw solution showed the percentage on the category very good, good, and enough sequence that is 45.8%, 45.8% and 8.3%. In the implementation stage titration shows the percentage in both excellent and good category in sequence that is 95.8% and 4.2%. Psychomotor analysis result in practicum determination of ascorbic acid level with iodimetry method obtained psychomotor ability average student get good category with percentage 54.2% and at very good category having percentage 45.8%.  Keywords: Psychomotor Skills, Iodimetry, Ascorbic Acid.